Placebo and nocebo effects in the neurological practice - Caroline Bittar; Osvaldo J.M. Nascimento (Arquivos de Neuro-Psiquiatria)
Knowledge of placebo and nocebo effects is essential to identify their influence on the results in clinical practice and clinical trials, and thereby properly interpret their results. It is known that the gold standard of clinical trials research is the double-blind, placebo-controlled, randomized clinical study. The objective of this review is to distinguish specific from non-specific effects, so that the presence of positive effects in the group that received placebo (placebo effect) and the presence of adverse effects in the group receiving placebo (nocebo effect) lead to confounding in interpreting the results. Placebo and nocebo effects have been considered in neurological diseases such as depression, pain, headache, multiple sclerosis, epilepsy. As placebo and nocebo effects are also present in clinical practice, the purpose of this review is to draw attention to their influence on neurological practice, calling attention to the development of measures that can minimize them.